Common Chinese Materia Medica Volume 6 - Ye, Huagu; Li, Chuyuan; Ye, Wencai; Zeng, Feiyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This sixth volume describes 226 species of 32 families of medicinal plants, which are commonly used in Chinese medicine. The most important species are Aquilaria sinensis and Daphne genkwa of Thymelaeaceae; Benincasa hispida, Siraitia grosvenorii, Trichosanthes kirilowii and Trichosanthes rosthornii of Cucurbitaceae; Camellia sinensis of Theaceae; Cleistocalyx operculatus, Eugenia caryophyllata and Rhodomyrtus tomentosa of Myrtaceae; Osbeckia chinensis of Melastomataceae; Quisqualis indica and Terminalia chebula of Combretaceae; Hypericum japonicum of Hypericaceae; Microcos paniculata of Tiliaceae; Hibiscus mutabilis of Malvaceae; Croton crassifolius, C. lachnocarpus, C. tiglium, Euphorbia humifusa, E. lathyris, E. pekinensis, Phyllanthus emblica and Sauropus spatulifolius of Euphorbiaceae. In each specie, it introduces the scientific names, medicinal names, morphologies, habitats, distributions, acquisition and processing methods of these medicinal plants, the content of medicinal properties, therapeutic effects, usage and dosage of these medicinal plants, and attaches unedited color pictures and pictures of part herbal medicines of each species. This book series has 10 volumes in total, which covers over 2000 kinds of Chinese medicines that are commonly used. These volumes not only introduce the efficacy function and some prescriptions of the medicines, but also introduce the biological characteristics of them in detail with clear photos of the habitats, so that readers can identify them in the field. Apart from the growing environment, the books expound the distribution areas and other information to facilitate researches and other applications. The volumes are targeted at readers of general interests and it is also of high referential value for scientific researcher and teachers. It can be used as a guide to researchers, clinical doctors, and students in the department of pharmaceutics and traditional Chinese medicine.
Aquilaria sinensis and Daphne genkwa of Thymelaeaceae -- Benincasa hispida, Siraitia grosvenorii, Trichosanthes kirilowii and Trichosanthes rosthornii of Cucurbitaceae -- Camellia sinensis of Theaceae -- Cleistocalyx operculatus, Eugenia caryophyllata and Rhodomyrtus tomentosa of Myrtaceae -- Osbeckia chinensis of Melastomataceae -- Quisqualis indica and Terminalia chebula of Combretaceae -- Hypericum japonicum of Hypericaceae -- Microcos paniculata of Tiliaceae -- Hibiscus mutabilis of Malvaceae -- Croton crassifolius, C. lachnocarpus, C. tiglium, Euphorbia humifusa, E. lathyris, E. pekinensis, Phyllanthus emblica and Sauropus spatulifolius of Euphorbiaceae.
Keywords: Pharmacy; Medicine; Plants$1 (BEvolution.s; Pharmacy; Clinical Medicine; Plant Evolution; Materia Medica